Morbidity and mortality in patients undergoing lower limb arthroplasty surgery during the initial surge of the COVID-19 pandemic in the UK at a single- speciality orthopaedic hospital. (2021) - Agrawal, Y.; Vasudev, A.; Sharma, A.; Cooper, G.; Stevenson, J.; Parry, M. C.; Dunlop, D.
No abstract available